ORIENTĂRI STRATEGICE PRIVIND RENOVAREA ÎNVĂŢĂMÂNTULUI SUPERIOR DIN REPUBLICA MOLDOVA - USM ADMIN (Moldova State University, 2008)
By the present research we are trying to present a pertinent analysis of actual situation of higher education in Republic of Moldova in European context. In the consequence of these findings we are suggesting one set of changes target at assurance of better development in the near future. Quality competitiveness and skill must be appreciated as foundations for the increasing role of each university and of higher education as a system in view of professional integration assurance of future graduates.